Behavioral plasticity is not significantly associated with head volume in a wild Chestnut Thrush (Turdus rubrocanus) population. Issue 1 (December 2016) - Zhao, Qingshan; Sun, Yuehua
Abstract Background The drivers of intraspecific variation in behavioral plasticity are poorly known. A widely held hypothesis is that brain size is positively correlated with behavioral plasticity. Methods A total of 71 Chestnut Thrushes (Turdus rubrocanus ) were caught in the wild population. We quantified behavior plasticity of activity of individuals measured in the same cage across two contexts (common and with a novel object stimulation), using a random regression analysis. We then investigated whether head volume (a proxy for brain size) was associated with behavioral plasticity in activity level using Spearman rank-order correlation. Results We found no significant evidence that activity plasticity was associated with relative head volume. There was no sex difference in head volume or in variance in head volume. Conclusions We speculate that the absence of an association between brain volume and activity behavior plasticity may result from the inaccuracy of using external skull measurements to estimate brain size, or from a particular part of the brain being responsible for plasticity in activity level.